(untitled) (Fiep Bulletin - online, 2015)
The activity of the military police officer by its very essence presupposes an activity where physical conditioning derives from a "sine qua non" to performing the mission. Thus, the purpose of the present study was to analyze the level of awareness of 70 military police officers (10 officers and 60 recruits)belonging to the 2nd Military Police Battalion (MPB) with respect to the importance of physical activity and professional performance. The simple random selection represented 40.32% of the full operational strength of battalion headquarters, located in Mossoró/RN/Brazil. The participants completed questionnaires and underwent interviews. The results indicate that, despite the unanimous awareness by the military police officers of the benefits of physical exercise on professional performance, there was no regular practice of this activity.